Paragon of excellence : Luther's sermons on I Peter - Ngien, Dennis, 1958- (Fortress Press, 2023)
"Ngien demonstrates that, for Martin Luther, the apostle Peter stood alongside John and Paul as a preacher of "the genuine and pure gospel." Luther's sermons on 1 Peter illustrate the range and depth of the reformer's mature theological thought. Peter's epistle stands as what Luther considered one of the "foremost books" of the New Testament"--